Genetics of Menkes Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Fibroblast cultures from 12 unrelated patients with classical Menkes disease, an X-linked disorder of copper metabolism, were analyzed for mutations in the MNK gene at the Howard Hughes Medical Institute, University of California, San Francisco.